2018
DOI: 10.1111/hojo.12243
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Contract Killers: A Narrative‐Based Approach

Abstract: Previous attempts to determine contract killers’ behaviour have not benefited from any formal psychological framework of behavioural distinction. The Narrative Action System model (NAS model; Canter and Youngs 2009) offers an empirical basis for differentiating contract killings and examining the psychological underpinnings of different contract killer styles. The model identifies four major narrative offender types: Professional, Revenger, Hero, and Victim. The present study aims to examine whether these them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Lastly, it would be worth exploring the psychological narratives of missing persons in order to understand underlying emotions and roles that may contribute to the decision to go missing. A number of studies have shown the importance of narratives with offenders (Ioannou, 2006;Ioannou, Canter, Youngs & Synnott, 2015;Ioannou, Canter & Youngs, 2017;Ioannou, Synnott, Lowe & Tzani-Pepelasi, 2018;Yaneva, Ioannou, Hammond & Synnott, 2018). While behavioural narratives have been explored with missing children (Payne, 1995) and missing adults (Bonny, Almond & Woolnough, 2016) both explorations are focused on behavioural differentiations as opposed to…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Lastly, it would be worth exploring the psychological narratives of missing persons in order to understand underlying emotions and roles that may contribute to the decision to go missing. A number of studies have shown the importance of narratives with offenders (Ioannou, 2006;Ioannou, Canter, Youngs & Synnott, 2015;Ioannou, Canter & Youngs, 2017;Ioannou, Synnott, Lowe & Tzani-Pepelasi, 2018;Yaneva, Ioannou, Hammond & Synnott, 2018). While behavioural narratives have been explored with missing children (Payne, 1995) and missing adults (Bonny, Almond & Woolnough, 2016) both explorations are focused on behavioural differentiations as opposed to…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…However, it has been reported (Youngs, Ioannou, & Eagles, ) that specialisation is represented through expressive and instrumental offenders, although if this relates to geo‐behaviour remains unclear. It would be useful to examine the criminal narratives of these two groups of offenders as has been successfully applied in other studies (Ioannou, Canter, Youngs, & Synnott, ; Ioannou, Canter, & Youngs, ; Ioannou, Hammond, & Simpson, ; Ioannou, Synnott, Lowe, & Tzani‐Pepelasi, ; Ioannou, Synnott, Reynolds, & Pearson, ; Yaneva, Ioannou, Hammond, & Synnott, ). This would be in respect to their geographic profiles to ascertain if the lack of variation is geographic behaviour is consistent in their offender narrative.…”
Section: Discussionmentioning
confidence: 99%
“…If they are; then these items would be represented in similar regions and would provide evidence for distinct criminal narrative experiences in PD and psychopathic offenders. A number of studies from have found such MDS models to be productive in recent years (Ioannou, Canter, Youngs & Synnott 2015;Ioannou, Hammond & Simpson, 2015;Youngs, Ioannou & Eagles, 2016;Ioannou, Canter & Youngs, 2017;Ioannou, Synnott, Lowe & Tzani-Pepelasi, 2018;Yaneva, Ioannou, Hammond & Synnott, 2018, Synnott, Ioannou, Coyne & Hemingway, 2018).…”
Section: Discussionmentioning
confidence: 99%